The Study of bend losses in large pipes - Lambino, Silvino M. (1996)
The study focuses on the problem of estimation of bend losses in large pipes. It verifies the relative influence of the different variables that affect this phenomenon. The uniqueness of the study is that it uses large diameters of pipes as models. The study considered two plants of Hydroelectric Development Corporation (HEDCOR) as models for experiments -- the Bineng 1 and the Ampohaw Power Plants with conveyance pipe diameters of 1.01 m and 1.83 m, respectively. The variables which affect the flow behavior were grouped into dimensionless parameters by means of dimensional analysis. Four dimensionless parameters were developed -- the Euler's Number, the Reynold's Number, the angle of bend and the Relative radius. Regression analysis was used to determine the functional relationships and the degree of association among the variables. Only two important parameters were determined to have significant effect on bend losses in large pipes -- the angle of bend and the Relative radius. The study hopes to contribute to the understanding of the occurrence of losses in bends specially in large pipes. In general, the results will prove useful in the hydraulic analysis and design of large piping systems. Specifically, it will benefit Hydroelectric Development Corporation (HEDCOR), the patron and employer of the researcher, which is involved in the implementation of mini-hydro projects.
Thesis (M.S. in Water Resources)--University of the Philippines, Diliman.
Keywords: Pipe bending; Hydraulic engineering; Pipe